Use of an Automated Nested Multiplex Respiratory Pathogen PCR Panel Postmortem in the Pediatric Forensic Setting1. Issue 5 (25th January 2017) - Baker, Tiffany; Schandl, Cynthia; Presnell, Susan Erin; Madory, James; Nolte, Frederick S.; Batalis, Nicholas
Abstract: Respiratory pathogens have been detected in forensic investigations using multiple techniques; however, no study has examined the use of automated, nested, multiplex polymerase chain reaction (ANM‐PCR), commonly used in living patients, in the forensic setting. This retrospective study assessed the utility of ANM‐PCR in detecting respiratory pathogens in the pediatric forensic setting. Respiratory samples from 35 cases were tested for up to 20 respiratory pathogens. 51.4% of these cases yielded a positive ANM‐PCR result, 20% of which were considered the cause of or contributory to death. The most commonly detected pathogens were rhinovirus/enterovirus and respiratory syncytial virus, and these were the only pathogens determined to play a significant role in cause of death. The sampled sites and postmortem intervals tested did not affect the likelihood of a positive or negative test. ANM‐PCR panels are effective, affordable, and rapid ancillary tools in evaluating cause of death in the forensic pediatric population.